Using the method of inverse growth calculations to determine the age composition of catches for certain species of marine commercial fish - A. O. Zolotov (Известия ТИНРО, 2024)
New method for constructing size-and-age keys is proposed and tested on the data on size composition of yellowfin sole in commercial catches in the Patience Bay in 1950–2024, with the age of fish determined using the inverse growth calculations techniques. The method makes it possible to get a correct size-and-age key sufficient for estimating the age composition in catch on results of mass measurements when collection of age-recording samples is not available, and at the same time allows to neutralize an effect of fishing gear selectivity. The method was practically used in cases of pacific cod in the South Kuril fishing area and in the Japan Sea, yellowfin sole in Sakhalin waters, rock sole of genus Lepidopsetta in waters at the Kuril Islands and in the western Bering Sea, and pacific herring in the South Kuril area. The method may be useful for solving practical tasks of calculation the age composition in catches and subsequent assessments of stock and allowable catch volume for marine fish species.